EXPLORING THE IMPACT OF FINANCIAL ATTITUDES, FINANCIAL KNOWLEDGE, AND PERSONALITY ON FINANCIAL MANAGEMENT BEHAVIOR AMONG SMALL AND MEDIUM ENTERPRISES (SMES) - Ni Putu Yeni Astiti; Wibawa, Ida Bagus Artha Sada; Gama, Agus Wahyudi Salasa (Jurnal Mebis, 2023)
Financial behavior is a way that everyone practices to treat, manage, and use the financial resources they possess. There are several factors that influence financial management behavior such as financial attitude, financial knowledge and personality. This research aims to know the influence of financial attitude, financial knowledge and personality on the behavior of financial management on UMKM. The population in this study is all UMKM. Determination of samples with saturated sampling technique with the number of samplings of as many as 37 UMKM participants. Data collection methods with observations, interviews, documentation, and questionnaires. The data analysis technique used is double linear regression analysis. The results of the test showed that the financial attitude has a positive and significant influence on the behavior of financial management on UMKM. Financial knowledge has a positive and significant influence on the behavior of financial management on UMKM. Personality has a positive and significant influence on the behavior of financial management on UMKM